Defining timeliness in care for patients with lung cancer: a scoping review. Issue 4 (7th April 2022) - Ansar, Adnan; Lewis, Virginia; McDonald, Christine Faye; Liu, Chaojie; Rahman, Muhammad Aziz
Abstract : Objectives: Early diagnosis and reducing the time taken to achieve each step of lung cancer care is essential. This scoping review aimed to examine time points and intervals used to measure timeliness and to critically assess how they are defined by existing studies of the care seeking pathway for lung cancer. Methods: This scoping review was guided by the methodological framework for scoping reviews by Arksey and O'Malley. MEDLINE, EMBASE, CINAHL and PsycINFO electronic databases were searched for articles published between 1999 and 2019. After duplicate removal, all publications went through title and abstract screening followed by full text review and inclusion of articles in the review against the selection criteria. A narrative synthesis describes the time points, intervals and measurement guidelines used by the included articles. Results: A total of 2113 articles were identified from the initial search. Finally, 68 articles were included for data charting process. Eight time points and 14 intervals were identified as the most common events researched by the articles. Eighteen different lung cancer care guidelines were used to benchmark intervals in the included articles; all were developed in Western countries. The British Thoracic Society guideline was the most frequently used guideline (20%). Western guidelines were used by the studies in Asian countries despite differences in the health system structure. Conclusion: This review identified substantial variations in definitions of some of the intervals used to describe timeliness of care for lung cancer. The differences in healthcare delivery systems of Asian and Western countries, and between high-income countries and low-income-middle-income countries may suggest different sets of time points and intervals need to be developed.